Rosemary Leaves as a Dietary Supplement for Growth in Broiler Chickens - Ghazalah, A.A.; Ali, A.M. (International Journal of Poultry Science, 2008)
This study was conducted to investigate the use of Rosemary leaves meal as a natural growth promoter in broiler diets on bird performance and immunity. RLM was added in either grower (7-28 day) or finisher (29-49day) diets at three concentrations (0.5, 1.0 and 2.0%). A total of 200 one-day old unsexed Arbor Acres chicks were assigned equally into four treatment groups, with five replicates of 10 chicks each. Chemical analysis of RLM showed a CF content of 19.4% of which 15.89% was present as cellulose. The essential oil of RLM ranged between 1.4-1.6% and the main active components were camphor (11-16%), alpha pinene (15-20%) and cineole (30-35%) which has a high degree of inhibition against many bacteria and fungi. Compared to control, chicks fed 0.5 % RLM exhibited higher body weights, greater weight gain, and better feed conversion during the experimental period as well as better physical properties of the chicken meat. Moreover, 0.5% dietary rosemary increased plasma total protein, albumin and globulin while decreasing glucose, total lipids and cholesterol content. RLM additions did not affect enzymatic activity related to liver and kidney functions. RLM stimulated thyroid function, as evidenced by increased plasma levels of T3, T4 compared to controls. Antibody production against sheep red blood cells was improved and the percentage of the lymphoid organs was increased compared to controls. Increasing the dietary level of RLM more than 0.5% lowered growth and the digestibility of most nutrients. Thus, low levels of dietary RLM could be safely used in broiler diets to promote growth and to impart healthful constituents to the consumer.